İstanbul'da Bir Mahallede Yaşayan Kadınaların Meme Kanseri Riskleri ve KKMM Eğitiminin Etkinliği - (:unkn) unknown (My University, 2014)
Amaç: The purpose of this study to determine the risks associated with breast cancer in women who live in a neighborhood in Istanbul, and to evaluate the effectiveness of breast self -examination (BSE) training. Yöntem ve Gereçler: This study was designed by using a half-experimental model, with women over the age of 18 who visited the community health center in a district of Istanbul, during March / April 2012. Sample selection was not implemented, and 169 women who voluntarily participated in the study were included. Data was collected by face-to-face interview technique with Demographic Survey Form , Breast Cancer Risk Assessment Form and BSE Training Assessment Scale . After risk assessment, women who wanted to learn BSE (n=109) were given a practical training program lasting approximately 20 minutes that was prepared together with expert consults. Bulgular: 32.1% of the participants regularly performed BSE. Out of those who do not use regular self-examination, 15.4% thought BSE was unnecessary, 44% was afraid to examine herself, and 40.7% did not know how to apply BSE. The mean breast cancer risk score was 135.64±61.33. There were statistically significant differences between breast cancer risk score and the educational status, marital status, and menstrual status. A statistically significant difference was found in pre- and post-training BSE Training Assessment Scale scores. Sonuç: The breast cancer risk score was low among women included in this study. However, the vast majority of women did not perform BSE, and those who did were using either irregular or improper practice. It was detected that implementation of planned and in-person training programs were quite effective.

Objective: The purpose of this study to determine the risks associated with breast cancer in women who live in a neighborhood in Istanbul, and to evaluate the effectiveness of breast self -examination (BSE) training. Materials and Methods: This study was designed by using a half-experimental model, with women over the age of 18 who visited the community health center in a district of Istanbul, during March / April 2012. Sample selection was not implemented, and 169 women who voluntarily participated in the study were included. Data was collected by face-to-face interview technique with Demographic Survey Form , Breast Cancer Risk Assessment Form and BSE Training Assessment Scale . After risk assessment, women who wanted to learn BSE (n=109) were given a practical training program lasting approximately 20 minutes that was prepared together with expert consults. Results: 32.1% of the participants regularly performed BSE. Out of those who do not use regular self-examination, 15.4% thought BSE was unnecessary, 44% was afraid to examine herself, and 40.7% did not know how to apply BSE. The mean breast cancer risk score was 135.64±61.33. There were statistically significant differences between breast cancer risk score and the educational status, marital status, and menstrual status. A statistically significant difference was found in pre- and post-training BSE Training Assessment Scale scores. Conclusion: The breast cancer risk score was low among women included in this study. However, the vast majority of women did not perform BSE, and those who did were using either irregular or improper practice. It was detected that implementation of planned and in-person training programs were quite effective.
Breast Cancer Risks and Effectiveness of BSE Training among Women Living in a District of İstanbul
Keywords: Cerrahi